Best practice in the prevention and management of paediatric respiratory syncytial virus infection - Drysdale, Simon B. (Ther Adv Infect Dis, 2016)
Respiratory syncytial virus (RSV) infection is ubiquitous with almost all infants having been infected by 2 years of age and lifelong repeated infections common. It is the second largest cause of mortality, after malaria, in infants outside the neonatal period and causes up to 200,000 deaths per year worldwide. RSV results in clinical syndromes that include upper respiratory tract infections, otitis media, bronchiolitis (up to 80% of cases) and lower respiratory tract disease including pneumonia and exacerbations of asthma or viral-induced wheeze. For the purposes of this review we will focus on RSV bronchiolitis in infants in whom the greatest disease burden lies. For infants requiring hospital admission, the identification of the causative respiratory virus is used to direct cohorting or isolation and infection control procedures to minimize nosocomial transmission. Nosocomial RSV infections are associated with poorer clinical outcomes, including increased mortality, the need for mechanical ventilation and longer length of hospital stay. Numerous clinical guidelines for the management of infants with bronchiolitis have been published, although none are specific for RSV bronchiolitis. Ribavirin is the only licensed drug for the specific treatment of RSV infection but due to drug toxicity and minimal clinical benefit it has not been recommended for routine clinical use. There is currently no licensed vaccine to prevent RSV infection but passive immunoprophylaxis using a monoclonal antibody, palivizumab, reduces the risk of hospitalization due to RSV infection by 39–78% in various high-risk infants predisposed to developing severe RSV disease. The current management of RSV bronchiolitis is purely supportive, with feeding support and oxygen supplementation until the infant immune system mounts a response capable of controlling the disease. The development of a successful treatment or prophylactic agent has the potential to revolutionize the care and outcome for severe RSV infections in the world’s most vulnerable infants.